Human bondage tracing its roots in India - Mishra, L., 1941-; Sage eBooks (New Delhi ; London : SAGE, 2011)
This book is about human freedom and dignity, the quintessence of human existence. It emphasizes how bonded labour is linked to issues like poverty, hunger, denial of minimum wage and the caste system.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Peonage -- India; Poor -- India -- Social conditions -- 21st century; Land tenure -- India; Social justice -- India; Electronic books